Question
upstudy study bank question image url

13. \( 2 x^{2}+8 x-60=4 \)

Ask by Daniel Colon. in the United States
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solutions are \( x = -8 \) or \( x = 4 \).

Solution

We start with the equation:   2x² + 8x – 60 = 4 Step 1: Subtract 4 from both sides to set the equation to zero.   2x² + 8x – 60 – 4 = 0   2x² + 8x – 64 = 0 Step 2: Divide the entire equation by 2 to simplify.   x² + 4x – 32 = 0 Step 3: Factor the quadratic equation. We look for two numbers that multiply to –32 and add to 4. The numbers 8 and –4 work since:   8 × (–4) = –32  and  8 + (–4) = 4 Thus, we factor the equation as:   (x + 8)(x – 4) = 0 Step 4: Solve each factor equal to zero. For x + 8 = 0:   x = –8 For x – 4 = 0:   x = 4 So, the solutions to the equation are:   x = –8 or x = 4.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Let's first simplify the equation by moving all terms to one side. Here’s how it looks after rearranging: \[ 2x^2 + 8x - 60 - 4 = 0 \] This simplifies to: \[ 2x^2 + 8x - 64 = 0 \] Now, we can divide through by 2 to make it easier: \[ x^2 + 4x - 32 = 0 \] Next, we can use the quadratic formula \( x = \frac{{-b \pm \sqrt{{b^2 - 4ac}}}}{2a} \). Here, \( a = 1 \), \( b = 4 \), and \( c = -32 \). So, let’s find the discriminant: \[ b^2 - 4ac = 4^2 - 4(1)(-32) = 16 + 128 = 144 \] Now substituting values into the quadratic formula: \[ x = \frac{{-4 \pm \sqrt{144}}}{2(1)} = \frac{{-4 \pm 12}}{2} \] This gives us two potential solutions: 1. \( x = \frac{{8}}{2} = 4 \) 2. \( x = \frac{{-16}}{2} = -8 \) So, the final solutions are \( x = 4 \) and \( x = -8 \). Now, you’ve got the answers—feel free to reach out if you need more on this topic!

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy